Prolonged Application of Continuous Passive Movement Improves the Postoperative Recovery of Tibial Head Fractures: A Prospective Randomized Controlled Study. (16th February 2022) - Kabst, Christiane; Tian, Xinggui; Kleber, Christian; Amlang, Michael; Findeisen, Lisa; Lee, Geoffrey; Zwingenberger, Stefan
Abstract : Background and Purpose . Tibial head fracture (THF) rehabilitation is still a challenge in clinical practice. Short-term use of continuous passive motion (CPM) postoperatively for THFs can increase knee range of motion (ROM) immediately, and its effect on enhanced rehabilitation also ended when the CPM application was discontinued. The aim of this study was to investigate the effect on the recovery of prolonged use of CPM in the postoperative treatment of THFs. Methods . 60 patients with THFs were randomly and equally divided into the CPM group and non-CPM group. Both groups immediately received CPM and conventional physical therapies during hospitalization. After discharge, the non-CPM group was treated with conventional physical therapy alone, while the CPM group received conventional physical training in combination with CPM treatment. At 6 weeks and 6 months postoperatively, the primary outcome which was knee ROM and the secondary outcome which was knee functionality and quality of life were evaluated. Results . The CPM group had a significantly increased ROM at both follow-up time points. The Knee Society Score, UCLA activity score, and the EuroQoL as well as the pain analysis showed significantly better results of the CPM group than the non-CPM group. Conclusions . The prolonged application of CPM therapy is an effective method to improve the postoperative rehabilitation of THFs.